A research agenda to underpin malaria eradication. - Alonso, P; Brown, G; Arevalo-Herrera, M; Binka, F; Chitnis, C; Collins, F; Doumbo, O; Greenwood, B; Hall, B; Levine, M; Mendis, K; Newman, R; et al. (2011)
The interruption of malaria transmission worldwide is one of the greatest challenges for international health and development communities. The current expert view suggests that, by aggressively scaling up control with currently available tools and strategies, much greater gains could be achieved against malaria, including elimination from a number of countries and regions; however, even with maximal effort we will fall short of global eradication. The Malaria Eradication Research Agenda (malERA) complements the current research agenda--primarily directed towards reducing morbidity and mortality--with one that aims to identify key knowledge gaps and define the strategies and tools that will result in reducing the basic reproduction rate to less than 1, with the ultimate aim of eradication of the parasite from the human population. Sustained commitment from local communities, civil society, policy leaders, and the scientific community, together with a massive effort to build a strong base of researchers from the endemic areas will be critical factors in the success of this new agenda.